Uncovering Alternative Ways of Maslow’s Hierarchy of Needs in Bessie Head’s “The Prisoner Who Wore Glasses” - Yosafat Andrew Gabrian Kameo (Lingua Susastra, 2024)
This study explores the process of achieving self-actualization in Brille, a character in Bessie Head's short story 'The Prisoner Who Wore Glasses,' who manages to fulfill higher-order needs (e.g., esteem, belonging) despite being deprived of basic necessities e.g., physical security during his imprisonment. We utilize Maslow's hierarchy of needs as a framework, employing a qualitative descriptive method to analyze the short story and elucidate Brille's need fulfillment. By examining how Brille adapts and finds meaning in extreme circumstances, this research proposes an alternative perspective on self-actualization, potentially demonstrating that even without fulfilling basic needs entirely, individuals can achieve higher-level needs. This contributes to the understanding of human adaptability in psychology and literature, suggesting that extreme situations may not always hinder personal growth.